(untitled) (Politeja, 2017)
The Jagiellonian Idea and the Project for the Future The Polish community suffers from weakening national bonds and therefore it has difficulties with defining its identity. Grandiose declarations are an embarrassing confirmation of this fact. No great idea capable of raising a future project for Poland is apparent. Is the Jagiellonian Idea capable of strengthening bonds, perhaps of giving impulse to a metamorphosis? Can it offer a project for tomorrow? Only what will be accepted by collective recognition as a project designed to ensure the existence of the national community has future. And by ‘existence’ I mean not only a verbalized identity, but also the capacity to carry out necessary changes independently. The article presents the view that the Jagiellonian Idea does not rest on facts, but on an imagined picture of the one-time Rzeczpospolita. It presents a thesis about the connection between the flourishing of that state and the acceleration of transformations tied to the dialogic vortex generated by the Baltic-Black Sea axis of concentration. The failure of that project is ascribed to the changed circumstances, and perhaps to the insufficient energy elicited by this dialogic vortex. The experience of the Rzeczpospolita as a European project, in turn, indicates the road we may take today toward the completion of the transformation begun in 1989.